2012
DOI: 10.1158/0008-5472.can-12-0044
|View full text |Cite
|
Sign up to set email alerts
|

RANK Induces Epithelial–Mesenchymal Transition and Stemness in Human Mammary Epithelial Cells and Promotes Tumorigenesis and Metastasis

Abstract: Paracrine signaling through receptor activator of NF-kB (RANK) pathway mediates the expansion of mammary epithelia that occurs during pregnancy, and activation of RANK pathway promotes mammary tumorigenesis in mice. In this study we extend these previous data to human cells and show that the RANK pathway promotes the development of mammary stem cells and breast cancer. Overexpression of RANK (FL-RANK) in a panel of tumoral and normal human mammary cells induces the expression of breast cancer stem and basal/st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
159
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(198 citation statements)
references
References 43 publications
23
159
1
6
Order By: Relevance
“…Recent studies suggested an involvement of RANKL in disease pathophysiology of chronic lymphoid leukemia (CLL) and multiple myeloma as well as metastatic spread of solid tumors (19)(20)(21)(22)(23)(24)(25)32), but nothing was yet known on the role of the RANK-RANKL molecule system in AML. In this study, we analyzed RANKL expression on primary AML cells by flow cytometry and selected malignant cells among PBMCs of leukemia patients by staining for CD33 and CD34.…”
Section: Expression Of Rankl In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested an involvement of RANKL in disease pathophysiology of chronic lymphoid leukemia (CLL) and multiple myeloma as well as metastatic spread of solid tumors (19)(20)(21)(22)(23)(24)(25)32), but nothing was yet known on the role of the RANK-RANKL molecule system in AML. In this study, we analyzed RANKL expression on primary AML cells by flow cytometry and selected malignant cells among PBMCs of leukemia patients by staining for CD33 and CD34.…”
Section: Expression Of Rankl In Amlmentioning
confidence: 99%
“…The TNFR family member receptor activator for NF-kB (RANK; TNFRSF11A) and its ligand (receptor activator for NF-kB ligand; RANKL) are mainly known for their key role in regulating bone metabolism (15,16) but were also found to influence the interaction of dendritic cells (DCs) and T cells as well as the pathophysiology of hematopoietic malignancies and metastasis of solid tumors (17)(18)(19)(20)(21)(22)(23)(24)(25). Notably, available data indicate that RANK is also expressed on NK cells (26), but to date nothing is known regarding the functional relevance of RANK-RANKL interaction for NK cell reactivity.…”
mentioning
confidence: 99%
“…I hypothesize that repeated activation of these pathways during the luteal phase of menstrual cycles promotes breast carcinogenesis. Some of these such as amphiregulin 98 , receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL) 99 and inhibitor of DNA binding 4 (ID4) 100 have indeed been implicated in the genesis of distinct human breast cancer subtypes. Interfering pharmacologically with menstrual cycle-induced activation of the breast (as described above), may be of particular use in young patients with breast cancer.…”
Section: Progesterone Signalling and Breast Cancermentioning
confidence: 99%
“…-/low СОК [27]. Межклеточные и клеточно-матриксные взаимодей-ствия крайне важны для поддержания и выживания СОК при метастазировании.…”
Section: Cd24unclassified